A randomized, controlled clinical trial of an intravesical pressure‐attenuation balloon system for the treatment of stress urinary incontinence in females. Issue 2 (16th January 2015) - Wyndaele, Jean‐Jacques; De Wachter, Stefan; Tommaselli, Giovanni A.; Angioli, Roberto; de Wildt, Michel J.; Everaert, Karel C. M.; Michielsen, Dirk P.J.; Van Koeveringe, Gommert A.
Abstract : Aims: Evaluate the efficacy, safety, and tolerability of a novel pressure‐attenuation balloon for the treatment of female stress urinary incontinence (SUI) using a prospective, randomized, single‐blind, multi‐center design, evaluated at 3 months. Methods: Sixty‐three females with SUI were randomized 2:1 to treatment with a balloon (N = 41) or sham procedure (N = 22). The sham (control) entailed the same procedure without the deployment of a balloon. Endpoints were evaluated at 3 months and included a composite endpoint that required both ≥10 point increase in the 22‐item Incontinence Quality of Life Survey (I‐QOL) and ≥50% decrease in provocative pad weight. Additional endpoints included incontinence episode frequency, and PGII assessment. Results: In an ITT analysis, 63% of women in the treatment group achieved the composite endpoint, compared to 31% in the Control Group ( P  = 0.0200). In a per protocol analysis, 81% of women in the treatment arm had a 50% decrease in pad weight test vs. 45% in the Control Group ( P  = 0.0143); 41.6% of the treatment patients were dry on pad weight test (≤1gram) vs. 0% in the Control Group ( P  < 0.001), and 58% of treated patients reported improvement on a PGII assessment versus 25% of women in the Control Group ( P  = 0.025). Adverse events in the treatment group included dysuria (14.6%), gross hematuria (9.8%), and UTI (7.3%). Conclusions: This minimally invasive treatment for female SUI with an intravesical pressure‐attenuation balloon was safe and effective. The concept of pressure attenuation as a therapy for SUI is valid and feasible for those patients that can tolerate the balloon. Neurourol. Urodynam. 35:252–259, 2016 . © 2015 The Authors. Neurourology & Urodynamics published by Wiley Periodicals, Inc.